The relationship between employee benefits and job satisfaction among employees in hotel industry at Temerloh, Pahang Darul Makmur / Anis Asnida Subri - Subri, Anis Asnida (Faculty of Business and Management, 2020)
This research paper aimed to investigate the relationship between employee benefits and job satisfaction among employees in hotel industry at Temerloh. Pahang Darul Makmur. This study used disproportionate stratified random sampling technique and the response rate was 92.4%. 61 respondents completed the survey questionnaire that was adopted from Robles (2018). SPSS V-20 was used to analyze the questionnaire in order to determine the result. Most of the respondents were female, aged between 20-30 years old and their basic salary were between RM 1.000 - RM 2,000. The findings showed that there was a significant and moderate relationship between employee benefits and job satisfaction among employees (r=0.56, p<.05). In addition, there was also significant and moderate relationship between pension funds and job satisfaction (r=0.40, p<.05). However, the findings indicated that there was a strong relationship between work-life balance and job satisfaction (r=0.62, p<.05). Generally, the employees agreed that attractive pension schemes could attract quality workers (M= 3.61, SD=1.09). The findings also shows that having flexible work schedules increases employee satisfaction (M=3.67, SD=1.21). It is recommended that the top management should improve allowance, holiday trip, leave management and other health benefits. Future research should increase sample size by focusing on other industries such as manufacturing or agriculture industry, study other elements of employee benefits and focus on other area such as the whole Pahang or Peninsular Malaysia in order to gain more comprehensive result